Metallic Ni nanoparticles embedded in hierarchical mesoporous Ni(OH)2: A robust and magnetic recyclable catalyst for hydrogenation of 4-nitrophenol under mild conditions. (15th May 2019) - Zhang, Ningxin; Wang, Xiangwen; Geng, Longlong; Liu, Zhongmin; Zhang, Xiuling; Li, Chunhui; Zhang, Dashuai; Wang, Zhigang; Zhao, Guoming
Graphical abstract: Ni NPs embedded in hierarchical Ni(OH)2 nanoarchitecture, fabricated via a facile solid redox strategy, provide dual advantages as a robust catalyst and a magnetically recoverable entity for the hydrogenation of 4-nitrophene under mild conditions. Abstract: The design of non-noble metal catalysts with high catalytic activity and stability is highly important for heterogeneous catalysis. Herein, we report a kind of Ni nanoparticles embedded in a 3D nanoarchitecture of Ni(OH)2, which was synthesized via an solid state redox strategy. The obtained material exhibited an interconnected pore structure and high surface area, thus displaying excellent catalytic activity and stability for the hydrogenation of 4-nitrophenol (4-NP) under mild conditions (1 atm and room temperature). The reaction rate constant and activation energy of the catalyst were determined to be 151.3 × 10 −3  min −1 and 42.3 kJ mol −1, respectively. Moreover, Ni/Ni(OH)2 also exhibited relatively high superparamagnetism properties; it could be separated facilely by using an external magnet and could be reused for at least ten times without obvious deactivation, exhibiting high reusability.